PENERAPAN MODUL ABAH UMI “MAHIR MERAWAT” UNTUK DETEKSI FAKTOR RESIKO BBLR TERHADAP PENGETAHUAN IBU HAMIL - Dewi Andariya Ningsih (Universitas Muhammadiyah Kudus, 2021)
Babies become focused in every health program because they are in a period of growth and development, and at all times face survival threats such as pain and death. The obstacles encountered in the field related to infant mortality in Situbondo Regency, one of which is community knowledge about high risk babies (especially low birth weight babies, 2500 grams /BBLR) is still low BBLR is still the highest cause of death in infants in Situbondo Regency. The purpose of this research is to produce an educational media product in the form of bblr risk detection module in pregnant women that can increase the knowledge of pregnant women. Wilcoxon Test results showed positive ranks indicating that all respondents gained increased knowledge after being given the intervention and the result of p-value = 0.000 0.05 so it can be said that there is a difference between pre test and post test on The Use of Module Abah Umi Adept care. For media validation 3.8 so that Abah Umi Module